Insights into phylogenetic divergence of Dalbergia (Leguminosae: Dalbergiae) from Mexico and Central America - Sotuyo, Solange; Pedraza-Ortega, Euler; Martínez-Salas, Esteban; Linares, José; Cabrera, Lidia (Frontiers in Ecology and Evolution, 2022)
The pantropical genus Dalbergia includes more than 250 species. Phylogenetic studies of the group are scarce and have only included two or three species distributed in Mexico. We obtained herbarium samples of Mexican, Central American and South American species (sourced from MEXU). In addition, sequences of genbank accessions were used to complement the study. Using ITS, matK and rbcL sequences from 384 accessions comprising species from America, Asia and Africa were sampled to evaluate phylogenetic relationships of Mexican species and infrageneric classifications based on morphological data. Phylogenetic analyses suggest that the genus Dalbergia is monophyletic, originated in South America. The species distributed in Mexico are not a monophyletic clade, but are divided into four clades with affinities to South American and Asian species clades. There is no correlation between geography and large-scale phylogeny. The estimated ages of the Mexican and Central America clades ranged from 11.32 Ma (D. granadillo clade) to 1.88 Ma (D. ecastaphyllum clade). Multiple long-distance dispersal events should be used to explain the current genus distribution.